2012
DOI: 10.1016/j.pain.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of positive and negative affect in recovery from spine surgery

Abstract: Consistent evidence supports a significant association between lower positive affect and higher negative affect and increased pain and disability in adults with chronic pain. However, examining this relation in surgical populations has received little empirical consideration. The primary purpose of this study was to determine whether preoperative and postoperative positive and negative affect predict pain, disability, and functional status after spine surgery. A secondary objective was to assess the relation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 77 publications
4
37
1
Order By: Relevance
“…Their statistical techniques did not account for greater comorbidities among demented patients. Patients with depression were hospitalized nearly 1 day shorter than the other patients, which is different from some prior studies [15,35]. Given the small effect size, this finding may be spurious.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Their statistical techniques did not account for greater comorbidities among demented patients. Patients with depression were hospitalized nearly 1 day shorter than the other patients, which is different from some prior studies [15,35]. Given the small effect size, this finding may be spurious.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, previous research has demonstrated that depression was markedly associated with poor long-term outcomes such as increased pain intensity, pain-related disability, and stiffness after TKA and spine surgery and that it correlated strongly with magnitude of disability in patients with orthopaedic trauma [8,15,35].…”
Section: Introductionmentioning
confidence: 99%
“…Acute pain outcomes (e.g., 24 - 48 hours post-surgery) and use of non-study analgesic treatments should be collected even though the primary aim of the study is to investigate the prevention of CPSP. These data can contribute to our understanding of whether acute pain predicts chronic pain and whether different acute factors contribute to the transition from acute to chronic pain (i.e., 24 – 72 hours to 3 months) than those that contribute to the persistence of chronic pain (i.e., 6 months to 1 year), which has been investigated in previous studies [87,146]. …”
Section: Design Considerations In the Context Of 4 Illustrative Prmentioning
confidence: 89%
“…Seebach et al (71), too, reported distinctly different effects of PA and NA in a longitudinal study of spinal surgery patients. Whereas pre-surgery PA and NA were not related to post-surgery outcomes, post-surgery PA, but not NA, significantly predicted higher postoperative functional status at 3 month follow-up.…”
Section: The Influence Of Pa Relative To Na In the Experience Of Painmentioning
confidence: 99%